2021
DOI: 10.1002/dc.24823
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy outcomes and the impact of repeat fine needle aspiration of thyroid nodules with Bethesda category III cytology: A multicenter experience

Abstract: Background: The clinical management of Bethesda III category thyroid nodules has some undefined points and differs among centers and conflicting malignancy rates are present in the literature. The aim of this study was to investigate the Bethesda category III thyroid nodule outcomes in our centers, to determine malignancy rates and also to evaluate clinical and sonographic features which may help to predict malignancy.Methods: This retrospective study included 333 patients with thyroid nodules who had Bethesda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Several studies have demonstrated the importance of repeat FNA in thyroid nodules with an initial AUS diagnosis. Repeat FNA establishes a definitive diagnosis (TBSRTC category II or VI) in up to 50% of nodules with an initial diagnosis of AUS, reducing unnecessary surgical intervention in benign nodules and providing useful pre‐operative information for malignant nodules 10,11,15,16 . However, a notable portion of nodules remained as AUS after repeat aspiration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated the importance of repeat FNA in thyroid nodules with an initial AUS diagnosis. Repeat FNA establishes a definitive diagnosis (TBSRTC category II or VI) in up to 50% of nodules with an initial diagnosis of AUS, reducing unnecessary surgical intervention in benign nodules and providing useful pre‐operative information for malignant nodules 10,11,15,16 . However, a notable portion of nodules remained as AUS after repeat aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they claimed that repeat FNA did not improve the PPV of Afirma GEC testing of AUS nodules 27 . On the contrary, some studies demonstrated an increased rate of histology‐proven malignancy in thyroid nodules with pre‐operative repeat FNA while reducing unnecessary surgical treatment of benign thyroid nodules 11,16 . Further, other authors note that repeat FNA cytology can guide the selection of cytologically indeterminate thyroid nodules that warrant molecular test (GEC) 12,13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the probable causes of discrepancies between reported results in that respect. Some studies showed a similar frequency of cancers in patients treated surgically after or without rFNA [ 21 , 22 , 23 ]; others indicated an increased rate of malignancy after rFNA, non-significantly [ 8 , 24 , 25 , 26 , 27 , 28 , 29 ] or significantly [ 20 , 30 , 31 , 32 , 33 ] and there are reports that suggested slightly lower malignancy rates in patients undergoing surgery after rFNA in comparison to those treated directly after the diagnosis of category III [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%